Overexpression of OsARD1 improves submergence, drought and salt tolerances of seedling through the enhancement of ethylene synthesis in rice - Liang, Shanshan; Xiong, Wei; Yin, Cuicui; Xie, Xiaodong; Jin, Ya-jun; Zhang, Siju; Yang, Bo; Ye, Guoyou; Chen, Shouyi; Luan, Wei-jiang (Frontiers Media, 2019)
Acireductone dioxygenase (ARD) is a metal binding metalloenzyme and involved in the methionine salvage pathway. In rice, OsARD1 binds Fe2+ and catalyzes the formation of 2-Keto-4-methylthiobutyrate (KMTB) to produce methionine, which is an initial substrate in ethylene synthesis pathway. Here, we report that overexpression of OsARD1 elevates the endogenous ethylene release rate, enhances the tolerance to submergence stress and reduces the sensitivity to drought, salt and osmotic stress in rice. OsARD1 is strongly induced by submergence, drought, salinity, PEG6000, and mechanical damage stresses, and exhibits high expression in senescent leaves. Transgenic plants overexpressing OsARD1 (OsARD1-OE) display fast elongation growth to escape the submergence stress. The ethylene content is significantly maximized in OsARD1-OE plants compared with the wide type. OsARD1-OE plants display increased shoot elongation and inhibition of root elongation under the submergence stress and grow in dark due to increase of ethylene. The elongation of coleoptile under anaerobic germination is also significantly promoted in OsARD1-OE lines due to increase of ethylene. The sensitivity to drought and salt is reduced in OsARD1-OE transgenic lines. Water holding capacity is enhanced and the stomata and trichomes on leaves increase in OsARD1-OE lines to contribute the reduction of the sensitivity to abiotic stresses. Drought and salt tolerance and ethylene synthesis related genes are upregulated in OsARD1-OE plants. Subcellular localization shows that OsARD1 displays strong localization signal in cell nucleus, suggesting OsARD1 may interact with the transcription factors. Taken together, the results provide the understanding of the function of OsARD1 in ethylene synthesis and abiotic stress response in rice